A Contribution Toward the Adaptation and Validation of the Entrepreneurial Self-Efficacy Scale in Italy and Portugal. (November 2017) - Spagnoli, Paola; Santos, Susana C.; Caetano, António
Entrepreneurial self-efficacy (ESE) seems to play a key role in the entrepreneurial career choice. The main goal of this study is to examine the reliability and validity of the ESE Scale proposed by McGee, Peterson, Mueller, and Sequeira both in Italy and Portugal. In particular, this study aims to strengthen and extend previous evidence of the Italian version of the ESE Scale and to assess its psychometric properties in Portugal. Furthermore, it aims at investigating the differences between two groups of participants both in Italy and Portugal: entrepreneurs and students. Construct, convergent, and discriminant validity of the ESE Scale were assessed through confirmatory factorial analysis and multigroups confirmatory factorial analysis using structural equation modeling. Configural, full metric, and partial scalar invariance were achieved. Moreover, correlational analysis, reliability analysis, and one-way analysis of variance were conducted. The findings support the use of the ESE Scale in Italy and Portugal for research and practical purposes. Limitation and suggestion for further research are also discussed.